Advances in clinical NK cell studies: Donor selection, manufacturing and quality control. (2nd April 2016) - Koehl, U.; Kalberer, C.; Spanholtz, J.; Lee, D. A.; Miller, J. S.; Cooley, S.; Lowdell, M.; Uharek, L.; Klingemann, H.; Curti, A.; Leung, W.; Alici, E.
ABSTRACT: Natural killer (NK) cells are increasingly used in clinical studies in order to treat patients with various malignancies. The following review summarizes platform lectures and 2013–2015 consortium meetings on manufacturing and clinical use of NK cells in Europe and United States. A broad overview of recent pre-clinical and clinical results in NK cell therapies is provided based on unstimulated, cytokine-activated, as well as genetically engineered NK cells using chimeric antigen receptors (CAR). Differences in donor selection, manufacturing and quality control of NK cells for cancer immunotherapies are described and basic recommendations are outlined for harmonization in future NK cell studies.